2015
DOI: 10.3389/fgene.2015.00306
|View full text |Cite
|
Sign up to set email alerts
|

Rice transcriptome analysis to identify possible herbicide quinclorac detoxification genes

Abstract: Quinclorac is a highly selective auxin-type herbicide and is widely used in the effective control of barnyard grass in paddy rice fields, improving the world's rice yield. The herbicide mode of action of quinclorac has been proposed, and hormone interactions affecting quinclorac signaling has been identified. Because of widespread use, quinclorac may be transported outside rice fields with the drainage waters, leading to soil and water pollution and other environmental health problems. In this study, we used 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…reported that a P450 gene, CYP72A31 , conferred tolerance to ALS‐inhibiting herbicides in rice and Arabidopsis. CYP72A was also found to be associated with pyroxsulam resistance in Lolium species, and quinclorac tolerance in rice . The CYP72A subfamily is conserved in angiosperms, contributing to secondary metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…reported that a P450 gene, CYP72A31 , conferred tolerance to ALS‐inhibiting herbicides in rice and Arabidopsis. CYP72A was also found to be associated with pyroxsulam resistance in Lolium species, and quinclorac tolerance in rice . The CYP72A subfamily is conserved in angiosperms, contributing to secondary metabolism .…”
Section: Discussionmentioning
confidence: 99%
“…Among the four genes implicated in plant-insect interactions, Cytochrome P450 family, transposon protein (LOC_Os10g37160) is a member of the large family of genes. Plant genes of this family are also reported to be involved in herbicide tolerance (Xu et al 2015 ), chemical defense and hormone biosynthesis. In our earlier study another copy of Cytochrome P450 gene (Os03g0658800) was found upregulated five fold in rice variety Suraksha with Gm11 gene at both 24 and 120 hai with GM biotype1 (Rawat et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…LOC_Os04g27430 and LOC_Os08g07100 are reported to be induced by BPH feeding and influence antixenosis in rice Rathu Heenati (Kamolsukyunyong et al 2013 ). The specific gene under study, LOC_Os08g07080 was found induced following fall armyworm feeding on leaves of Nipponbare japonica rice (Yuan et al 2008 ) and also reported to be involved in detoxification of auxin-type herbicide quinchlorac (Xu et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in UGT expression after florpyrauxifen-benzyl, glyphosate, and quinclorac treatments indicate the involvement of this gene in the adaptation response to these herbicides. In rice, the glucosyltransferase gene was reported to be involved in the glucose conjugation of phenolics and possible quinclorac detoxification [107,108]. A glucosyltransferase was identified and enabled as a potential transcriptional marker for quick diagnosis of metabolic resistance to mesosulfuron in Alopecurus aequalis [18].…”
Section: Memory Of Gene Expression and Sensitivity Reduction In E Comentioning
confidence: 99%